RIFM fragrance ingredient safety assessment, Isoborneol, CAS Registry Number 124-76-5. (October 2015) - Api, A.M.; Belsito, D.; Bhatia, S.; Bruze, M.; Calow, P.; Dagli, M.L.; Dekant, W.; Fryer, A.D.; Kromidas, L.; La Cava, S.; Lalko, J.F.; Lapczynski, A.; et al.
Abstract: The use of this material under current use conditions is supported by the existing information. This material was evaluated for genotoxicity, repeated dose toxicity, developmental toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity, skin sensitization potential as well as environmental safety. Repeated dose toxicity was determined to have the most conservative systemic exposure derived NOAEL of 15 mg/kg/day based on a gavage 13-week subchronic toxicity study conducted in rats on a read across analog resulting in a MOE of 1000 considering 100% absorption from skin contact and inhalation. A MOE of >100 is deemed acceptable. Highlights: Isoborneol safety assessment based on RIFM's criteria. Safety assessment based on 7 Human health endpoints plus environmental. Repeated dose toxicity was determined to give the most conservative systemic derived NO[A]EL. An acceptable MOE was obtained.